2004
DOI: 10.1111/j.0022-202x.2004.23407.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Wheal and Flare by Tea Tree Oil: Complementary Human and Rodent Studies

Abstract: When applied 20 min after injection of histamine into human forearm skin, tea tree oil (TTO) reduces the developing cutaneous vascular response. In this study, the effect of TTO on inflammatory microvascular changes was dissected at the base of an experimental blister on rat skin. 1,8-Cineole, representing 2% of TTO, reduced vascular changes induced by sensory neuropeptides released when the distal portion of a cut sciatic nerve was electrically stimulated. The pre-terminal modulatory effect of 1,8-Cineole was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 23 publications
1
43
0
2
Order By: Relevance
“…In human studies, tea tree oil reduced experimentally induced skin reactions (nickel-or histamine-induced contact hypersensitivity) [50][51][52], which was suggested to be a result of decreases in vasodilation, microvascular blood flow and plasma extravasation [53]. Three non-acne clinical studies also report reduced inflammation following application of tea tree oil products for treating haemorrhoids [54], ocular demodecosis [55] and tinea [56].…”
Section: Properties Of Tea Tree Oil Contributing To Clinical Efficacymentioning
confidence: 99%
“…In human studies, tea tree oil reduced experimentally induced skin reactions (nickel-or histamine-induced contact hypersensitivity) [50][51][52], which was suggested to be a result of decreases in vasodilation, microvascular blood flow and plasma extravasation [53]. Three non-acne clinical studies also report reduced inflammation following application of tea tree oil products for treating haemorrhoids [54], ocular demodecosis [55] and tinea [56].…”
Section: Properties Of Tea Tree Oil Contributing To Clinical Efficacymentioning
confidence: 99%
“…Erythema and flare associated with nickel-induced contact hypersensitivity in humans are also reduced by neat TTO but not by a 5% TTO product, product base, or macadamia oil (119). Work has now shown that terpinen-4-ol, but not 1,8-cineole or ␣-terpineol, modulates the vasodilation and plasma extravasation associated with histamine-induced inflammation in humans (94).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…A study by Murakami et al (2000) identified citrus nobiletin as an effective, topicallyapplied inhibitor of skin inflammation, oxidative dermal stress response, and skin tumor promotion. A similar effect has been demonstrated using tea tree oil, which contains many of the same essential oils as those derived from citrus peel, in a parallel rodent-human study (Khalil et al, 2004). One explanation for the success shown by essential oils in skin treatment may be the extraordinary ability of these oils to penetrate the skin to the subsurface layers where active skin growth (and presumably inflammatory processes) occur.…”
Section: Citrus Peel By-products As Sources Of Antioxidants and Immunmentioning
confidence: 54%